Natural Products: The Secondary Metabolites - James R. Hanson (Tutorial chemistry texts, 17., 2003)
"Natural products are compounds that are produced by living systems and the secondary metabolites are those which give particular species their characteristic features. These natural products include polyketides, terpenoids, phenylpropanoids, alkaloids and antibiotics. The study of these natural products has played a major part in the development of organic and medicinal chemistry and we are now starting to understand the important ecological role that these compounds have. The aim of this book is to describe the major features of these compounds and the way in which chemical and physical methods have been used to establish their structures and then to show how these structures can be rationalised in biosynthetic terms." "The elucidation of the structures of natural products brings together many elements taught in courses on functional group chemistry, stereochemistry and elementary spectroscopy. This book will therefore be welcomed by lecturers and students of second-year chemistry courses."--Jacket